Sources and oxygen consumption of particulate organic matter settling in oyster aquaculture farms: Insights from analysis of fatty acid composition. (5th June 2021) - Hatakeyama, Yuji; Kawahata, Tatsuya; Fujibayashi, Megumu; Nishimura, Osamu; Sakamaki, Takashi
Abstract: We investigated the composition of fatty acids and oxygen consumption rate (OCR) of the settling particulate organic matter (POM) and its potential sources (suspended POM, oyster biodeposits, fouling mussel biodeposits, POM attached on oysters and farm gears) in oyster farms, and estimated their relative contribution to the settling POM using a stable isotope mixing model. The settling POM was lower in both the content of algal-originating fatty acids and OCR compared with those of the potential sources. Furthermore, the content of fatty acids and OCR of settling POM were lower inside than outside the oyster farms. The settling flux of POC was 2–18 times higher inside than outside the oyster farms, with the settling POM estimated to consume on average 5 times more oxygen in the bottom layers. The contribution of oyster biodeposits to the settling POM inside the farms was equivalent to that of other potential sources. Our study highlighted that preventing recruitment and removing sessile organisms from the cultivated organisms and farm facilities such as mussels and microorganisms could be an effective strategy for reducing the amount of POM settling inside the farms. Furthermore, we showed that the fatty acids marker would be a good indicator for predicting the potential of oxygen consumption of various POM sources. Highlights: The composition of sources of POM in settling POM differed among seasonal samplings. The relationship of fatty acids with consumption of oxygen changed across seasons. Contents of fatty acids and oxygen consumption per unit mass were lower in settling POM of oyster farms than in POM sources. Total oxygen consumed by settling POM per unit area was higher in oyster farms due to large settling flux of POM.